Beneficiary Satisfaction Analysis in Terms of Service Commitement and Satisfaction. - Andi Asrijal; Sandi Sandi; M. Awaluddin; Abdul Rahman; Sugian Nurwijaya (Universitas Negeri Makassar, 2021)
One of the public sector services that are currently being highlighted is the hospital. This organization which is engaged in the health sector is one of the backbones of the country in terms of providing health services to the community. The more complete the facilities and infrastructure of an organization or hospital, it will also have a positive impact on the level of satisfaction with the community. This study aims to analyze the effect of service commitment and service quality on performance through beneficiary satisfaction at task implementation unit Regional General Hospital Tenriawaru Bone. The results showed that the quality and service commitment of task implementation unit Regional General Hospital Tenriawaru greatly influenced the performance of all workers involved in the system. However, the negative relationship that occurs between user satisfaction and performance of task implementation unit Regional General Hospital Tenriawaru illustrates the lack of further communication between benefit users and task implementation unit Regional General Hospital Tenriawaru. Similarly, the results of the study concluded that the better the service quality of a hospital, the higher the patient satisfaction and vice versa. This study can be used as a consideration in improving the quality and commitment of services at task implementation unit Regional General Hospital Tenriawaru because there is still a negative relationship between benefit users and task implementation unit Regional General Hospital Tenriawaru.